Investigation of increasing fault Gas in excitation transformers - Che Muhamad Khabali, Mohd Khazani (2014)
This study is to carry out investigation on increasing fault gas in oil insulation in three similar excitation transformers in Tanjung Bin Power Plant; Transformer A, Transformer B, and Transformer C. The research covers the transformer oil sample collection, and the experiment of Dissolved Gas Analysis (DGA) in laboratory. Then, the DGA results as raw data are evaluated using two methods which are Duval Triangle and Rogers Ratio in order to interpret and estimate the possible internal fault that may present in all transformers. The research is also included with three mitigation procedures and one verification test on selected transformer respectively. First procedure study is replacing Transformer A with spare. Second method is oil insulation degasification from Transformer B. Third procedure is continued with high frequency of DGA monitoring of Transformer C. The results from all case studies are again interpreted and checked with Duval Triangle and Roger’s Ratio for before and after outcome comparison. In addition to, the investigation is widened with electrical diagnostics tests which are carried out on Transformer A in order to verify the root cause of internal fault. The decision of serviceability of all excitation transformers are successfully made by having a Transformer Health Index (THI) using the condition factors as mentioned above. It is concluded that, all excitation transformers are good to be keep in service with several recommendations.